2020
DOI: 10.3171/2019.12.spine191257
|View full text |Cite
|
Sign up to set email alerts
|

The true penalty of the waiting room: the role of wait time in patient satisfaction in a busy spine practice

Abstract: OBJECTIVEMost clinics collect routine data on performance metrics on physicians for outpatient visits. However, the relationship of these metrics with patient experience is unclear. The goal of this study was to investigate the relationships between the Consumer Assessment of Healthcare Providers and Systems Clinician and Group Survey (CG-CAHPS), the standard patient experience survey, and clinic performance metrics to understand the determinants of patient satisfaction and identify targets for improving patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…Patient wait times are an important indicator of healthcare service delivery, as long wait times have been shown to negatively impact access to care and patient satisfaction [1][2][3][4][5][6][7]. In particular, patients from medically underserved populations not only have a higher burden of disease but also experience longer wait times [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Patient wait times are an important indicator of healthcare service delivery, as long wait times have been shown to negatively impact access to care and patient satisfaction [1][2][3][4][5][6][7]. In particular, patients from medically underserved populations not only have a higher burden of disease but also experience longer wait times [1,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported interventions aimed at patient access, care providers, and improving wait times in ambulatory settings to improve patient experience (3,(6)(7)(8). Prolonged wait time in the clinic is often a source of frustration for patients and can significantly impact patient experience scores negatively on surveys (9)(10)(11). We report our experience of optimizing patient flow in clinic resulting in sustained improvement in patient experience scores related to a visit in a busy clinic over 5 years.…”
Section: Introductionmentioning
confidence: 98%
“…Patient wait times are an important indicator of healthcare service delivery, as long wait times have been shown to negatively impact access to care and patient satisfaction [1][2][3][4][5][6][7] . In particular, patients from underserved and vulnerable populations not only have a higher burden of disease but also experience longer wait times 1,8,9 , which further exacerbates their medical conditions and outcomes.…”
Section: Introductionmentioning
confidence: 99%